Kelayakan Konstruksi Bangunan Trotoar di Kota Ambon - Tomia, Niati; Nendissa, Renny Heronia; Pattinasarany, Yohanes (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Sidewalks are road support facilities as stipulated in Law no. 22 of 2009 concerning Road Traffic and Transportation. The availability of sidewalks must provide safety and comfort for pedestrians passing through.Purposes of the Research: The purpose of writing this thesis is to find out and analyze (1) Does the sidewalk building in Ambon City meet the construction feasibility requirements in the provisions of laws and regulations.? and (2) What are the legal consequences if the sidewalk building does not meet the construction feasibility standards in the ptovisions of the legislations.? Methods of the Research: The type of research used in this study is normative juridical legal research, namely legal research conducted by examining library materials or secondary materials which consist of primary legal materials and secondary legal materials. These materials are arranged systematically, studied, then a conclusion is drawn in relation to the problem under study.Results of the Research: The results and discussion show that the construction of sidewalks in the city of Ambon does not meet the feasibility standards for the construction of sidewalks as stipulated in the Regulation of the Minister of Public Works Number 03/PRT/M/2014 concerning Guidelines for Planning, Provision and Utilization of Infrastructure and Facilities for Pedestrian Networks and Urban Areas, and Decree of the Director General of Highways No. 74/KPTS/Db/1999, Date, 7 December 1999 Concerning Ratification of One Technical Guideline of the Directorate General of Highways. Of course, this condition has legal consequences as stipulated in Article 44UU No. 28 of 2002 concerning Buildings in which there are administrative sanctions in the form of a) Written warning; b) Restrictions on development activities; c) Temporary or permanent suspension of construction implementation work; d) Temporary or permanent suspension of building use; e) Freezing of building construction permits; f) Revocation of building construction permit; g) Freezing of the certificate of proper function of the building h) revocation of the certificate of proper function of the building; or i) an order for the demolition of a building.